Estimation of fertility at the canton level in Costa Rica: application of a variant of the Brass Method - Carballo Murillo, Natalia (2014)
The purpose of this article is to validate a variant of the Parity/Fertility Brass method, for situations in which the census does not ask about fertility during the last year, comparing the synthetic indices of fertility at the canton level obtained with the implementation of the variant of the method, with the information of the cantonal fertility rates obtained by processing vital statistics. Information for the census of 1973, 1984, 2000 and 2011 will be used as well as the information of the vital statistics on births; year of occurrence was matched with census year, for Costa Rican women between 15-49 years. The variant to the method was to use children under one year of registered as if they were the births of the last twelve months. Despite the observed trend of the decline, in the difference of the ISF at cantonal level, it becomes evident that there is an overestimation, in some cases quite substantial of the ISF cantonal with the variant of the P/F method as compared to the data obtained with the births of vital statistics. Such a situation of decrease, in general, can be related to the improvement in the registration of births and in the voter registration and identification of children with patiently and multiple births.